Cryopreservation of Musa germplasm - Panis, Bartholomeus; Thinh, N.T.; International Network for the Improvement of Banana and Plantain (2001)
This publication describes cryopreservation methods developed for Musa tissue at KUL (Katholieke Universiteit Leuven, Belgium) and JIRCAS (Japanese International Research Centre for Agricultural Sciences). Detailed protocols are given for all steps to follow from the preparation of the plant material to the recovery and regeneration of whole plants. These methodologies are specific to the type of banana tissue to be cryopreserved: individual meristems, meristem clumps (cauliflower-like structures), embryogenic cell suspensions, and zygotic embryos. Each method is illustrated with figures and colour photographs. Advantages and limitations of each method are highlighted, and current perspectives for optimizing the methodologies presented are discussed. It is hoped that these guidelines will facilitate the adoption and use of the methodologies described. The publication includes bibliographical references and some useful practical information: composition of media and solutions, and list of the basic equipment needed.